In Situ Enzymatic Synthesis Of Collagen-Chitosan Hydrogel Using Ultrasonic Pretreated Collagen - Lau, Sin Mun (2019)
In recent years, injectable hydrogel has shown great potential for biomedical applications owing to its distinct properties of in situ gelation. In this research, ultrasonication was introduced to pretreat tendon collagen used in the project to reduce the size of fibrils and prevent fibril aggregation. The pretreated collagen (Col) was combined with chitosan (Chit) to improve the physical properties of hydrogels. Composite hydrogel was formed by oxidative coupling of the phenolic hydroxyl (Ph) groups in polymer chains using horseradish peroxidase (HRP) and hydrogen peroxide (H2O2). The resulting Col-Chit-Ph solutions were able to form rapid hydrogel via peroxidase-catalyzed crosslinking reaction. The concentration of HRP and H2O2 affected the gelation time of Col-Chit-Ph hydrogels. Besides, the Col to Chit (Col:Chit) ratio also significantly influenced the physical, in vitro and mechanical characteristics of composite hydrogels. The hydrogel with a higher composition of chitosan has faster gelation, higher mechanical strength, and lower degradability, but resulted in lower porosity of the hydrogel matrix. The results obtained in this study reveal the importance of the chitosan ratio to the Col-Chit-Ph injectable hydrogel composite. The most significant results were obtained in the conjugate hydrogel with Col:Chit ratio of 3:2, which has the highest cell growth rate compared to others after 5 days of incubations. Hence, this hydrogel has the potential for use in the biomedical fields as it is mechanically stable and supports cellular functions.